The problem of "the individual and society" in the context of the ideological and thematic orientation of the I-novel "Convenience store woman" - Prof. DSc Khalliyeva Gulnoz Iskandarovna; Teacher Petrosyan Naira Romanovna (Zien Journals, 2023)
This article devoted to the problem of "people and society" in the context of the ideological and thematic orientation of the I-novel "Convenience store woman" written by Sayaka Murata. This is not only subtle, ironic prose about everyday life, but also a sharp statement about being different from others and about disobeying social norms. "Convenience store woman" is an emphatically Japanese and at the same time universal story about how cruel the unwritten laws of society are. Sayaka Murata explores the boundaries of "normality" and the enormous pressure that people have been experiencing since childhood: the ordinary and even more bitter story of the main character Keiko is about how harmless stereotypes seem and how dangerous they really are
Keywords: Sayaka Murata; Convenience store woman; Japanese society; psychologist